Concurrent validity of the differential ability scales, second edition with the Mullen Scales of Early Learning in young children with and without neurodevelopmental disorders. Issue 5 (3rd July 2016) - Farmer, Cristan; Golden, Christine; Thurm, Audrey
Abstract : Estimates of intelligence in young children with neurodevelopmental disorders are critical for making diagnoses, in characterizing symptoms of disorders, and in predicting future outcomes. The limitations of standardized testing for children with developmental delay or cognitive impairment are well known: Tests do not exist that provide developmentally appropriate material along with norms that extend to the lower reaches of ability. Two commonly used and interchanged instruments are the Mullen Scales of Early Learning (MSEL), a test of developmental level, and the Differential Ability Scales, second edition (DAS-II), a more traditional cognitive test. We evaluated the correspondence of contemporaneous MSEL and the DAS-II scores in a mixed sample of children aged 2–10 years with autism spectrum disorder (ASD), non-ASD developmental delays, and typically developing children across the full spectrum of cognitive ability. Consistent with published data on the original DAS and the MSEL, scores on the DAS-II and MSEL were highly correlated. However, curve estimation revealed large mean differences that varied as a function of the child's cognitive ability level. We conclude that interchanging MSEL and DAS-II scores without regard to the discrepancy in scores may produce misleading results in both cross-sectional and longitudinal studies of children with and without ASD, and, thus, this practice should be implemented with caution.